2009
DOI: 10.3747/co.v16i3.304
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of IG-IMRT for Palliative Radiotherapy: A Single-Institution Experience

Abstract: minimize side effects, and can be planned relatively quickly. Delaying the start of radiotherapy because of a complicated treatment planning process does not make sense. For patients requiring palliative radiotherapy, specialized clinics have even been developed where treatment (with one or a few fractions of radiotherapy) is planned and administered on the same day that the consultation takes place 15 . Usually, fluoroscopic simulation and simple treatment approaches such as direct fields or parallel opposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Studies from several European countries, including Sweden, with similar health care systems and availability of resources have also identified problems related to radiotherapy referral [9,12,13,18]. It has long been felt that the proximity to cancer centres, perceived patient inconvenience, and waiting times for consultation and treatment are concerns for referring doctors, and these were confirmed in our survey [6,7,10,11,19]. However, we found that other factors also have a major influence on referral.…”
Section: Discussionsupporting
confidence: 61%
“…Studies from several European countries, including Sweden, with similar health care systems and availability of resources have also identified problems related to radiotherapy referral [9,12,13,18]. It has long been felt that the proximity to cancer centres, perceived patient inconvenience, and waiting times for consultation and treatment are concerns for referring doctors, and these were confirmed in our survey [6,7,10,11,19]. However, we found that other factors also have a major influence on referral.…”
Section: Discussionsupporting
confidence: 61%
“…This sophisticated level of RT delivery would be ideal for cases often seen within these clinics when targets assume challenging geometric configurations, when they approach sensitive structures (often in the reirradiation setting), or when they could benefit from dose escalation over conventional doses [40,41]. This sophisticated level of RT delivery would be ideal for cases often seen within these clinics when targets assume challenging geometric configurations, when they approach sensitive structures (often in the reirradiation setting), or when they could benefit from dose escalation over conventional doses [40,41].…”
Section: Incorporation Of Advanced Rt Technologiesmentioning
confidence: 99%
“…3,4 Radiotherapy (RT) is cost-effective compared with other available palliative treatments, [5][6][7][8] and is inversely correlated with hospital bed use at end of life. 9 PRT is one form of palliative medicine that has the potential to improve quality of life for patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%